INFORMATION SYSTEMS DESIGN SERVICES SAVINGS BANK MUAMALAT INDONESIA (BMI) - Sama Sama; Ir. Fitri Sjafrina, MMSI (Jurnal Sistem Informasi, 1998)
Service information system of savings that are run on the Bank Muamalat Indonesia (BMI) the describes the process of working on parts of a duty to serve on bank savings system. In addition, the proposed information system service savings, as the development of information systems service savings that are currently running. Proposed service information system displays a more balanced division of labor among the parts involved in serving the savings. This division  of labor using queuing time. Output shown is the work process more precise in giving its transactions are made.